The neuroprotective attribution of Ocimum basilicum: a review on the prevention and management of neurodegenerative disorders - Mohamed Ali Seyed; Siddiqua Ayesha; Norazrina Azmi; Fahad Mohamed Al-Rabae; Adel Ibrahim Al-Alawy; Othman Rashed Al-Zahrani; Yousef Hawsawi (SpringerOpen, 2021)
Abstract Background Bioactive principles from various natural resources including medicinal herbs have always played a crucial role in healthcare settings and increasingly became key players in drug discovery and development for many biopharmaceutical applications. Additionally, natural products (NPs) have immense arrangement of distinctive chemical structures with diverse functional groups that motivated numerous investigators including synthetic chemists to discover new therapeutic entities. Numerous pre-clinical investigations involving the animal models have evident the usefulness of these NPs against various human diseases including neurodegenerative disorders (NDs). Main text Ocimum basilicum Linn (O. basilicum L.), also known as sweet basil, is well practiced in traditional healthcare systems and has been used to treat various human illnesses, which include malaria, skin disease, diarrhea, bronchitis, dysentery, arthritis, eye diseases, and insect bites and emphasize the significance of the ethno-botanical approach as a potential source of novel drug leads With the growing interest in advanced techniques, herbal medicine and medicinal plants explorations are still considered to be a novel resource for new pharmacotherapeutic discovery and development. O. basilicum L and its bioactive principles including apigenin, eugenol, myretenal, β-sitosterol, luteolin, rosmarinic acid, carnosic acid, essential oil (EO)-rich phenolic compounds, and others like anthocyanins and flavones could be of therapeutic values in NDs by exhibiting their neuro-protective efficacy on various signaling pathways. The present comprehensive review collected various related information using the following searching engines such as PubMed, Science Direct, Google Scholar, etc. and focused mainly the English written documents. The search period comprised of last two decades until present. Conclusion Although these efficacious plant genera of prime importance and has potential medical and socioeconomic importance, yet the pivotal evidence for its neuroprotective potential in novel clinical trials remains lacking. However, with the available wealth of obtainable literature on this medicinal plant, which supports this review and concludes that O. basilicum L may function as a promising therapeutics for the treatment of NDs.